Research of the latest web-technologies and algorithms for site promotion - Егорова, Ирина Николаевна; Бондаренко, Елена Анатольевна (Eastern-European Journal of Enterprise Technologies, 2012)
Technologies for creation user interface, namely HTML5, CSS3, JavaScript, - are of great interest in modern WEB-design, because they can significantly extend the functionality of WEB-pages, supports the latest multimedia applications, while maintaining ease of reading the code for developer and clarity of performance for computers and devices. Search engine optimization is a set of measures to raise the site positions in search engine results for a particular search users. There is a need to determine the most efficient and effective way to search engine optimization so as to take into account the features of the filters used and the ranking algorithms of the leading search engines. Thus, the work aimed to an analytical study of the latest technology Web-design and analysis of the basic algorithms of promotion of sites seems to be actual. The aim of the analytical study conducted in the Master's work is the implementation of the comparison of methods and technologies for creating interactive Web-graphics in HTML5 - Canvas and SVG (Scalable Vector Graphics) and determine the most appropriate applications of technology in the Canvas and SVG Web-design and development of recommendations for new and experienced developers for use of a particular model of graphics in HTML5. As well as identifying key ranking factors Veduchi search, analysis of the mechanism of the search filters and determining the optimal algorithm of search engine optimization on the basis of the analytical study. Practical implementation based on Trials conducted an interactive multimedia training manual «HTML5/CSS3, JavaScript. Development of modern sites. "